The changing role of the U.S. military in space - Gonzales, Daniel, 1956- (Rand, 1999)
Growth in the technical capabilities of commercial and foreign space systems, potential exploitation of space by adversaries, increasing use of commercial space capabilities by U.S. forces, and continuing budget constraints are all changing the role of the U.S. military in space. The growth of commercial space markets, and the rapid privatization and increasing foreign ownership of commercial space assets, suggest that the Department of Defense must develop a long-term strategy to ensure adequate and secure access to commercial communications satellites and other commercial space resources. Space control will assume increasing importance in military operations, and space itself may become a theater of military operations. The United States should develop a long-term strategy to enable the U.S. military to deny space capabilities to potential adversaries. Such a strategy should rely on system or operational concepts that minimize collateral damage to commercial, civil, and third-party space assets and that do not violate existing arms control agreements or treaties. Space surveillance--the ability to precisely identify, track, and predict the position of objects in space --is an essential aspect of space control. Space control and changing space surveillance needs have implications for the Air Force as an institution.